EKSPERIMENTASI MODEL PEMBELAJARAN KOOPERATIF GROUP INVESTIGATION(GI) DAN THINK-PAIR-SHARE (TPS) PADA MATERI DIMENSI TIGA DENGAN PENDEKATAN PMRI DITINJAU DARI KREATIVITAS SISWA - Y Noenoek Andrijanti; Budiyono Budiyono; Dewi Retno Sari (Jurnal Pembelajaran Matematika, 2013)
Abstract:The purpose of this research are to know: 1) which one gives better achievement in mathematics, learning model of GI with IRME approach, learning model of TPS with IRME approach, or conventional learning model, 2) which one gives better achievement in mathematics, student who was high creativity, middle creativity, or low creativity, 3) for each category of student’s creativity (high, middle, and low), which one produces better achievement in mathematics, learning model of GI with IRME approach, learning model of TPS with IRME approach or conventional learning model. This research is quasi-experimental research with the research plan using factorial 3´3. The population of this research was all students in class X in SMA/MA Surakarta academic year 2012/2013. The sample-taking was done using stratified cluster random sampling. The instrument which was applied to obtain the data of the research was test, questionnaires, and documentation. The test instrument was used to know the mathematics achievement on three- dimensional material. Hence, questionnaires instrument was used to know the student’s creativity. The questionnaires instrument includes content validity, internal consistency and reliability. The test instrument includes content validity, level of difficulty, different power and reliability. The results of the research are (1) GI type of cooperative learning model with IRME approach provides better learning achievement than the TPS type with IRME approach, conventional learning in mathematic learning in three dimension material. The TPS type of cooperative learning provides the learning achievement as good as the conventional learning did in three dimension material of mathematic learning, (2) the students with high creativity level have mathematic learning achievement as good as those with medium creativity level, the students with medium creativity level have mathematic learning achievement as good as those with low creativity level, and the students with high creativity level have mathematic learning achievement better than those with low creativity level, (3) at each creativity level, the GI type of cooperative learning model application with IRME provided learning achievement better than both TPS type with IRME and conventional learning did. The TPS type of learning model with IRME approach provided learning achievement as good as the conventional learning did in three dimension material of mathematic learning. Keywords:GIlearning model, TPS, IRME, creativity.